(untitled) (London Journal of Research In Science: Natural and Formal, 2026)
The paper is utilyzing data from the SuperKamiokande solar neutrino detection experiment and analyses them by diffusion entropy analysis and standard deviation analysis to evaluate the scaling exponent of the probability density func tion. The result of analysis indicates that solar neutrinos are subject to L´evy flights. The paper derives the probability density function and the governing fractional dif fusion equation for solar neutrino L´evy flights in terms of Fox’s H-function. The con clusion of the paper is the question: Does SuperKamiokande Observe L´evy Flights of Solar Neutrinos?